(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This paper presents a functionaldesign and modeling of a successive approximation analog-to-digital converter(ADC) and its application in the conditioning circuit of the vibration energyharvester. The paper published on BMAS’09 highlighted the necessity of a smartdigital control to calibrate the system, which requires in turn an ultra lowpower supplied ADC. The harvester and the ADC are designed using a CMOS 0.35μmHigh Voltage technology and modeled in a mixed VHDL-AMS/ELDO environment. Thesupply voltage of the ADC is 2.5V. The whole system was simulated using a mixedsignal Advance MS simulator.